Enzyme activities and enhancement of plant nutrient content in vermicompost - Yan, Yi Wei (2013)
Nutrient recycling has been seen as a viable way to return nutrient both to the soil and plant. Recycling of organic wastes such as plant residues reduces the amount of wastes that enter the landfills. Vermicomposting has been widely accepted as an efficient, rapid and cost effective way in managing organic waste. The current study investigated the efficiency of earthworms Eudrilus eugeniae and Perionyx excavatus in vermicomposting rice straw. Vermicompost derived by P. excavatus was found to contain higher concentrations of total N, P, K and Mg. Available P, K and Mg was also higher in P. excavatus vermicompost. However E. eugeniae vermicompost was found to contain higher total and available Ca. Humic acid content was also found to be higher in E. eugeniae vermicompost. The experiment showed E. eugeniae took 134 days while P. excavatus took 171 days to complete vermicomposting. Though Perionyx excavatus vermicompost contains higher total and available plant nutrient, the rate of vermicompost generation by this species was relatively low compared to E. eugeniae. Subsequent experiment was conducted by comparing plant nutrient availabilities and humic acids content in vermicompost generated from different plant residues; grass clippings (GC), sago waste (SW) and rice straw (RS) using E. eugeniae as vermicomposting agent. Total P was lower in vermicomposts as compared to the controls, however, highest extractable P was found in RS vermicompost (0.33 ± 0.00 g/kg). SW vermicompost contained highest total Ca (22.79 ± 0.01 g/kg) compared to the GC (1.39 ± 0.01 g/kg) and RS (8.22 ± 0.06 g/kg) vermicompost. Significant positive correlations between nutrient contents in raw plant residues and vermicompost were observed for total N (r = 0.779), K (r = 0.998) and Ca (r = 0.997). The study showed that nutrient in initial wastes material affects the nutrient contents of vermicompost. This suggests that among the plant residues studied, vermicomposting of rice straw produced vermicompost with the highest plant extractable nutrient contents. The effect of storage on the enzymatic action and microbial activity in the vermicompost was also determined. RS vermicompost was stored for 6 months and samples were taken every month to analyse the microbial and enzymatic activity in the vermicompost. Microbial and enzyme activities (protease and phosphatase) in vermicompost were found to be relatively active indicating that application of vermicompost after 6 months post harvest may still stimulate N and P nutrient cycling in agricultural land. RS vermicompost was found to contain high amount of plant extractable nutrients which could be easily taken up by plants. Nevertheless when compared to inorganic fertilizers the nutrient content in vermicompost is still relatively lower. Therefore, an attempt was made to further improve the extractable nutrient in RS vermicompost by adding rock phosphate (RP) during vermicomposting. The extractable P was 24% higher in vermicompost with the addition of rock phosphate. In addition, extractable macronutrients N and K were found to be significantly higher in the final product of vermicomposting with the addition of rock phosphate. The research studied the various aspects that influence the quality of vermicompost. Based on the results obtained, an improvement in the macronutrient content in vermicompost has also successfully achieved. As an overall, the evidences raised for the current study proved that vermicomposting can be a viable technology in recycling organic wastes such as rice straw in Malaysia. This will benefit the farmers economically and contribute significantly in reducing open burning activity, thus creating a cleaner environment.